Good people : a novel [large type] - Sabit, Patmeena (Random House Large Print, 2026)
The Sharaf family is the picture of success. Prosperous, rich, happy. They came to this country as refugees with nothing more than the clothes on their backs. And now, after years of hard work, they live in the most exclusive neighborhood, their growing family attending the most prestigious schools. Zorah, the eldest daughter, is the apple of her father's eye. When an unthinkable tragedy strikes, everyone is left reeling and the family is thrust into the court of public opinion. There is talk that behind closed doors the Sharaf's happy household was anything but. Did the Sharaf family achieve the American dream? Or was the image of the model immigrant family just a façade? Like a literary game of ping-pong, Good People compels the reader to reconsider what might have happened even on the previous page. Told through a kaleidoscope of perspectives, it is a riveting, provocative, and haunting story of family-sisters, brothers, mothers, fathers, and the communities that claim us as family in difficult times.